Midline lethal granuloma: Case report and review of literature - Alzubaidee, Ali A.; Ahmed, Shaheen Ali (Zanco Journal of Medical Sciences (ZJMS), 2015)
Lethal midline granuloma syndrome is a clinical term used generally to describe a rare clinical entity, of unknown aetiology, characterized by progressive destruction of face, nose, para-nasal sinuses, and palate, oral and para-oral structures. Diagnosis is often difficult and requires expert clinical and histopathological examination of the lesion. A case of advanced high–grade lymphoma is reported as it was misdiagnosed and not treated properly for several months. After final diagnosis, a combined radio and chemotherapy were offered to the patient, but unfortunately the patient died because there was no response to treatment.